Security in the absence of a State: traditional authority, livestock trading, and maritime piracy in Somalia - Acharya, A; Harding, R; Harris, JA (SAGE Publications, 2020)
Without a strong state, how do institutions emerge to limit the impact of one group’s predation on another’s economic activities? Motivated by the case of northern Somalia, we develop a model that highlights the monitoring challenges that groups face in making cooperation self-enforcing, and two key factors that influence their likelihood of overcoming this challenge: the ratio of economic interests across productive and predatory sectors, and the existence of informal income-sharing institutions. Our model explains why conflicts between pirates and livestock traders can be resolved in the region of Somaliland, where the ratio of economic interests favors the productive sector and traditional institutions promote income sharing between groups, but not in the region of Puntland, where these conditions do not hold. The model also accounts for several of the empirical patterns in the relationships between piracy, livestock exports, and conflict in both regions.